Translation and Validation of a Chinese Version of the Mindfulness in Parenting Questionnaire (MIPQ) - Wu, Lei; Buchanan, Heather; Zhao, Yaping; Wang, Ping; Zhan, Zhao; Zhao, Boyao; Fan, Bijuan (Frontiers in Psychology, 2019)
Objective: To translate the Mindfulness in Parenting Questionnaire (MIPQ) into Standard Mandarin and then explore the reliability and validity of this newly-translated measure in a large sample of Chinese middle school parents. Methods: We translated the MIPQ using the forward-backward method and pilot tested it on a sample of parents of adolescent children in China. Following minor modifications, 662 Chinese parents (Mothers or Fathers) in two middle schools (children aged 12-16 years; one in the North and one in the South of China) completed the newly translated scale (C-MIPQ), as well as the Mindful Attention and Awareness Scale (MAAS) to test convergent validity. 121 participants completed the C-MIPQ again 2 weeks later to determine test-retest reliability. Results: Confirmatory factor analysis showed that the two-factor model indicated in the original study was a good fit (χ 2/df = 2.34, RMSEA = 0.045, GFI = 0.93, NFI = 0.91, CFI = 0.94, RFI = 0.88, IFI = 0.94). The total score of the scale and the scores of the two dimensions (‘Mindful discipline’ and ‘Being in the moment with the child’) were significantly positively correlated with the total score of the MAAS, demonstrating convergent validity (r=0.39 0.47, p<0.001). Cronbach’s α for the total scale was 0.93 (and 0.88 for the two dimensions of the C-MIPQ) indicating excellent internal consistency. Test-retest reliability was good (intra-class correlation of 0.83). Conclusion: The Chinese Version of the Mindfulness in Parenting Questionnaire (C-MIPQ) has sound psychometric properties and can be used as a tool to measure mindful parenting in parents of adolescents aged 12-16 years.